Aktualisasi Diri Remaja Dalam Novel Lan Asira Wahdi Karya Amal Ahmad Tha’amah: (Kajian Psikologi Sastra) - Zururi, Miftahullah Ilmy; Amsariah, Siti (DAS Institute, 2025)
This study analyzes the forms of adolescent self-actualization in the main character